Consumption of tryptophan-rich foods and quality of sleep in primary school students from a school in Lima, Peru - Caldart, Nino (2025)
During the COVID-19 pandemic, many aspects of children's lives were significantly impacted, including their sleep habits. Recent studies have hypothesized and demonstrated the direct impact of confinement on sleep quality, resulting in immune system impairment and the development of psychological disturbances.